KARAKTERISTIK PETROLOGI, GEOKIMIA STUDI DAN SIFAT KETEKNIKAN ANDESIT DI DAERAH TANJUNGSARI DAN SEKITARNYA, KECAMATAN PACITAN, KABUPATEN PACITAN, PROVINSI JAWA TIMUR - , SITI LAILI NAILUL FARIH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Andesite is one of mine commodity which the occurrence is abundant in Pacitan (big potential), it is mostly mined and used as construction material. In order to optimize on the usage of andesite as construction material and to establish the appropriate method for exploration that will be worked, therefore this research explain about petrogenesis of andesite, quality of andesite, and the correlation among characteristic of petrology, geochemical and engineering properties of andesite by using several methods. The methods are geological mapping, petrography analysis, chemical analysis (XRF and ICP-MS), engineering properties test (density, absorbed water, durability and compressive strength of rocks), and statistical analysis (correlation and regression). Andesite in Tanjungsari and surrounding area is belong to Arjosari Formation, above this andesite, conglomerate unit, siltstone unit, and sandy clay sediment unit was sedimented which bordered by uncorformity boundary. Andesite in research area is product of Tertiary volcanic activity, formed as lava from andesitic magma with 57,59 â 59,14 wt % SiO2 content and alkalinity from tholeiitic to calc-alkaline. This magma was formed in tectonic setting in subduction zone, precisely in calcalkaline island arc area. Source of magma derived from pikritic magma or olivine basalt from N-MORB mantle which experienced Rb, Ba, Th, and K enrichment from subducted crust, and through fractional crystallization process of olivine and clinopiroxene so caused magma composition changing into andesitic. The results of engineering properties test show that compressive strength of andesite in research area is categorized into weak, strong enough (moderately strong) and strong, and generally the quality of andesite is appropriate to standard of nature rocks for construction materials. The results of correlation and regression analysis give the trend of relation among character of petrology, geochemical and engineering properties of andesite, and give regression model.